2013
DOI: 10.1016/j.paid.2012.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Secondary psychopathy, but not primary psychopathy, is associated with risky decision-making in noninstitutionalized young adults

Abstract: Although risky decision-making has been posited to contribute to the maladaptive behavior of individuals with psychopathic tendencies, the performance of psychopathic groups on a common task of risky decision-making, the Iowa Gambling Task (IGT; Bechara, Damasio, Damasio, & Anderson, 1994), has been equivocal. Different aspects of psychopathy (personality traits, antisocial deviance) and/or moderating variables may help to explain these inconsistent findings. In a sample of college students (N = 129, age 18 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 38 publications
4
49
1
3
Order By: Relevance
“…Means in the current sample, displayed in Table 1, were comparable with those typically found in emerging adult samples with regards to child maltreatment exposure (Mitchell & Mazzeo, 2005), impulsivity (Dean et al, 2013), and BMI (Huang, Shimel, Lee, Delancey, & Strother, 2007). Emotional abuse and emotional neglect were the most commonly reported child maltreatment types, with 6.4% of the sample reporting moderate to severe levels of emotional abuse or emotional neglect.…”
Section: Resultssupporting
confidence: 57%
“…Means in the current sample, displayed in Table 1, were comparable with those typically found in emerging adult samples with regards to child maltreatment exposure (Mitchell & Mazzeo, 2005), impulsivity (Dean et al, 2013), and BMI (Huang, Shimel, Lee, Delancey, & Strother, 2007). Emotional abuse and emotional neglect were the most commonly reported child maltreatment types, with 6.4% of the sample reporting moderate to severe levels of emotional abuse or emotional neglect.…”
Section: Resultssupporting
confidence: 57%
“…The IGT, which is a measure of ‘real world’ risky decision‐making (Bechara et al ., ), is regarded as an appropriate task in order to investigate impulsivity and self‐regulation in patients with antisocial traits. Dean, Altstein, Berman, Constans, Sugar and McCloskey () found that risky decision‐making was related to participants with secondary psychopathy traits (antisocial behavior), but not primary psychopathy traits (lack of empathy). The IGT was originally developed to measure decision‐making in patients with ventromedial prefrontal cortex lesions (VPCL) (Bechara et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Given that their overall mean rejection rate did not differ from the other groups either, the offenders without psychopathy seem to be guided by the magnitude of the proposal's intrinsic distribution (what the proposer gets vs. what the responder gets) with a dislike of unequal outcomes, i.e., inequity aversion. Fairness is determined by payoffs available in the here and now, which may reflect the preference for immediate options, hinting at a hyperactivity of the impulsive system (Buckholtz et al, 2010; Dean et al, 2013). …”
Section: Discussionmentioning
confidence: 99%